2014
DOI: 10.1161/circresaha.114.302530
|View full text |Cite
|
Sign up to set email alerts
|

Cardiogenic Genes Expressed in Cardiac Fibroblasts Contribute to Heart Development and Repair

Abstract: Rationale Cardiac fibroblasts are critical to proper heart function through multiple interactions with the myocardial compartment but appreciation of their contribution has suffered from incomplete characterization and lack of cell-specific markers. Objective To generate an unbiased comparative gene expression profile of the cardiac fibroblast pool, identify and characterize the role of key genes in cardiac fibroblast function, and determine their contribution to myocardial development and regeneration. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
199
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 186 publications
(227 citation statements)
references
References 39 publications
(44 reference statements)
26
199
1
1
Order By: Relevance
“…A systematic dissection of the nature, roles and origins of cardiac SCA1 + cells remains to be performed. Recent single-cell expression profiling confirmed that the SCA1 + /PDGFRα + fraction of cardiac interstitial cells, probably derived from the epicardium (Chong et al, 2011;Furtado et al, 2014), is enriched in clonogenicity and multi-lineage differentiation after in vivo engraftment . However, cell retention after engraftment was low and it remains to be determined whether heterogeneity per se in the total SCA1…”
Section: Sca1 + Cells Side Population Cells and Cardiospheresmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic dissection of the nature, roles and origins of cardiac SCA1 + cells remains to be performed. Recent single-cell expression profiling confirmed that the SCA1 + /PDGFRα + fraction of cardiac interstitial cells, probably derived from the epicardium (Chong et al, 2011;Furtado et al, 2014), is enriched in clonogenicity and multi-lineage differentiation after in vivo engraftment . However, cell retention after engraftment was low and it remains to be determined whether heterogeneity per se in the total SCA1…”
Section: Sca1 + Cells Side Population Cells and Cardiospheresmentioning
confidence: 99%
“…Colonies and the larger stromal cell population also express some cardiac developmental transcription factors, including GATA4, TBX5, HAND1 and MEF2C, suggesting a cardiac identity and/or lineagecommitted state (Furtado et al, 2014;Noseda et al, 2015). Cultured cCFU-F show long-term growth through serial passage, reflecting their ability to self-renew, and display multipotency in vitro and in surrogate in vivo assays, including co-culture with ESCs to form teratomas and after injection into infarcted hearts (Chong et al, 2011;Noseda et al, 2015).…”
Section: Cardiospheresmentioning
confidence: 99%
“…However, fibroblasts have recently reached centre stage in regenerative medicine due to their capacity to be reprogrammed into alternative cell lineages Ieda et al, 2010Ieda et al, , 2009Nam et al, 2014Nam et al, , 2013aQian et al, 2013Qian et al, , 2012Takahashi et al, 2007;Takahashi and Yamanaka, 2006), their capacity to interact with other cell types in their microenvironment , and their ability to modulate disease processes (Furtado et al, 2014a;Takeda et al, 2010). As cardiac fibroblasts play a prominent role in heart scarring, it is essential to understand and control the activity of these cells in order to develop efficient treatments for heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…Our analysis of genomic regions that were available for TF interaction through ATAC-seq in endocardial lineages and bound by TBX20 in embryonic heart revealed overrepresentation of specific TF motifs. Several of these TFs, including NKX2-5, GATA4, MEF2, and TEAD, have been previously associated with TBX20 in adult cardiomyocytes and cardiac fibroblasts (31,34). Interestingly, motifs highly enriched near TBX20-binding sites within endocardial lineages included those recognized by the AP1 family, which contains JUN, FOS, ATF, and MAF proteins.…”
Section: Tbx20 Regulates the Endocardial Proliferation And Migratory mentioning
confidence: 99%
“…In addition, we found overrepresentation of motifs for GATA family TFs MAFA, a member of the bZIP family of TFs that includes AP1 factors MEF2C, homeodomain TFs NKX2-1 and NKX2-5, and TEAD TF-binding motifs ( Figure 5B and Supplemental Table 2). NKX2-5, GATA, MEF2, and TEAD TFs have been previously identified as cofactors of TBX20 in cell lines and adult heart, indicating a high level of functional conservation (3,30,31,33,34).…”
Section: Identification Of Tbx20-binding Sites Within Open Chromatin mentioning
confidence: 99%